2018
DOI: 10.1016/j.fcr.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Physical robustness of canopy temperature models for crop heat stress simulation across environments and production conditions

Abstract: Despite widespread application in studying climate change impacts, most crop models ignore complex interactions among air temperature, crop and soil water status, CO 2 concentration and atmospheric conditions that influence crop canopy temperature. The current study extended previous studies by evaluating T c simulations from nine crop models at six locations across environmental and production conditions. Each crop model implemented one of an empirical (EMP), an energy balance assuming neutral stability (EBN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 90 publications
(104 reference statements)
0
26
0
Order By: Relevance
“…The relatively low warming levels of the HAPPI scenarios (0.6 and 1.1°C above 1980–2010 global mean temperature) but high increases in [CO 2 ] suggest that CO 2 fertilization effects also dominate here (Kimball, ; O'Leary et al, ), but could be less, if nitrogen is limiting growth. However, the impacts here could be slightly overoptimistic with estimates of heat stress, as most of crop models do not account for well‐established canopy warming under elevated CO 2 (Kimball et al, ; Webber et al, ). Also, Schleussner et al () have shown that CO 2 uncertainties at 1.5 and 2.0°C, which is not considered here, are comparable to the effect of 0.5°C warming increments.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low warming levels of the HAPPI scenarios (0.6 and 1.1°C above 1980–2010 global mean temperature) but high increases in [CO 2 ] suggest that CO 2 fertilization effects also dominate here (Kimball, ; O'Leary et al, ), but could be less, if nitrogen is limiting growth. However, the impacts here could be slightly overoptimistic with estimates of heat stress, as most of crop models do not account for well‐established canopy warming under elevated CO 2 (Kimball et al, ; Webber et al, ). Also, Schleussner et al () have shown that CO 2 uncertainties at 1.5 and 2.0°C, which is not considered here, are comparable to the effect of 0.5°C warming increments.…”
Section: Discussionmentioning
confidence: 99%
“…SQ and S2 models do not include effects of [CO 2 ] on transpiration, though they are applied only to wheat. Seven models include algorithms to estimate crop canopy temperature (FA, L5, HE, SS, SQ, S2, and CR) allowing the interaction of high temperature, drought stress, and [CO 2 ] 22 . Key details and references of the model’s treatment of heat and drought stress are given in Supplementary Tables 5 and 6 .…”
Section: Methodsmentioning
confidence: 99%
“…High temperatures drive non-linear increases in vapor pressure deficit (VPD), raising evaporative demand and concurrently depleting subsequent water supply 21 . Nevertheless, questions remain about which crop level processes dominate these responses, as potentially confounding effects of higher temperature accelerating development and damaging reproductive organs were not explicitly controlled for, both of which are expected to be larger under drought stress conditions due to canopy heating 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Crop growth models often use air temperature in growth and phenology functions (Neukam et al, 2016), and these would need to be re-written using leaf/canopy temperatures. Furthermore, in a comprehensive multi-model study testing crop model skill at simulating canopy temperature, Webber et al (2018) show that the best performing models were able to explain only 30%-40% of variance in the difference between leaf and air temperatures (Webber et al, 2018).…”
Section: Modeling Leaf Temperaturementioning
confidence: 99%